Desenvolvimento inicial de plantas de trigo em resposta à associação com bactérias diazotróficas e níveis de irrigação por solução ácida (Research, Society and Development, 2020)
The cultivated species have ideal soil pH for absorption of nutrients and proper development, it is necessary to know the performance of nitrogen-fixing bacteria and promoting plant growth (PGPBs) at different levels of acidity, in order to increase the results to elevate crop yields with the use of technology inoculation of seeds of gramineous. Thereby, the present study aimed to determine the initial development of wheat seedlings subjected to inoculation with Azospirillum brasilense and Herbaspirillum seropedicae at different levels of acidity irrigating solution in autoclaved sand substrate. Adopted the randomized block design (RBD) in a 3x4 factorial design with three levels of acidity of the solution (pH 4.5, 5.5 and 6.5) and the second factor [without inoculation, seeds inoculated at the time of seeding with A. brasilense (AbV5), H. seropedicae (SmR1) and association of the two strains AbV5+ SmR1. Increased root length was detected at pH 4.5 compared to pH 5.5 and 6.5 regardless or not with A. brasilense and H. seropedicae. Inoculation with A. brasilense promotes greater diameter collect, regardless of the pH and increase in root volume to pH 6.5 alone or associated with H. seropedicae.